Assembly of an S-band FMCW doppler radar system for improved pedestrians detection - Muhd Ariffin, Nor Fatin; Ismail, Ahmad Fadzil; Mohd. Isa, Farah Nadia; Muslim, Aidy @ Mohamed Shawal (Science & Engineering Research Support Society (SERSC), 2017)
A Frequency Modulated Continuous Wave (FMCW) Doppler radar was assembled to detect passing-by pedestrians. Its operating frequency is at 2.4GHz with transmit power of 10.41dBm. Range resolution of the radar is 2.8meters at 53.2MHz signal bandwidth and chirp waveform of 40ms. The radar exploits Doppler principle to acquire the range and velocity information of targets whilst a Moving Target Indicator (MTI) pulse canceller is utilized to filter incoming noise signal. With the use of Chirp period-bandwidth product of Frequency Modulated (FM) waveform and deramping process, the radars’ Signal to Noise Ratio (SNR) was improved up to 42dB. The attained maximum range is about 200meters for target with Radar Cross Section (RCS) of 1m2 . The constructed radar is capable to measure speed of moving target at 0.645m/s and above with great accuracy. The radar can detect and determine position of pedestrians with 0.18% percentage error.